2018
DOI: 10.1111/rmir.12107
|View full text |Cite
|
Sign up to set email alerts
|

On the Corporate Demand for Insurance: Evidence From the Global Reinsurance Market

Abstract: In this article, we view the demand for reinsurance as a "special case" of the corporate demand for insurance. We analyze the extent to which reinsurance purchases by the global property-liability insurance industry vary across countries and assess the relative importance of country-level factors compared with firm-level factors. Using a data set consisting of 21,814 firm-year observations from 33 (developed and developing) countries during the period 2000-2012, we find that after controlling for firm-level fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…In accordance with the financial distress hypothesis of risk management, the study's panel data regression results indicated a negative significant relationship between leverage and income retention by Property and Liability insurance firms. These findings are in line with majority of the findings such as Altuntas et al (2018) and Curak et al (2014).…”
Section: Empirical Literature Reviewsupporting
confidence: 92%
“…In accordance with the financial distress hypothesis of risk management, the study's panel data regression results indicated a negative significant relationship between leverage and income retention by Property and Liability insurance firms. These findings are in line with majority of the findings such as Altuntas et al (2018) and Curak et al (2014).…”
Section: Empirical Literature Reviewsupporting
confidence: 92%
“…The amount of capital invested, and the reinsurance acquired must be balanced for the insurance companies because the capital requirements are impacted by this balance (Altuntas et al, 2018). In this way, a capital structure issue is the demand for reinsurance (Cummins et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, our dependent variable needs to be a proxy of reinsurance use. We use a measure that is common in the reinsurance literature and define the variable Reinsurance Ratio as the ratio between reinsurance premiums ceded and the sum of the direct premiums written and reinsurance premiums assumed (Mayers and Smith 1990;Choi and Weiss 2005;Cole and McCullough 2006;Wang et al 2008;Shiu 2011;Lee and Lee 2012;Garven et al 2014;Lin et al 2015;Yanase and Limpaphayom 2017;Altuntas et al 2018).…”
Section: Dependent Variablementioning
confidence: 99%